PENGARUH SEMANGAT KERJA PEGAWAI TERHADAP MINAT BACA MASYARAKAT PADA KANTOR ARSIP DAN PERPUSTAKAAN DAERAH KOTA TERNATE. - Nurlaila, Nurlaila (Jurnal MS, 2014)
This study aims to analyze and determine the effect the morale of the public interest which occurred in the Office of Archives and Library area of Ternate, carried out using quantitative research methods. In particular the implementationÂ of the Library experiencing empty or decrease in public interest. Based on the research results, public interest is affected by this employee morale can be folded on the magnitude of the coefficient of determination (r ) of 0.224,Â this figure shows that employee morale can influence society's interest in readingis 22.4%, and the remaining 77.6% influenced by other variables not examined inÂ this study. hypothesis test results are known tÂ of 7.128 at sig t of 0.002 atÂ significance level alpha (Î± = 0.05). it is stated that morale has significant influence on society reading interest, meaning that the hypothesis is proven andÂ accepted. Based on research results is expected that the leadership of the Regional Office ofÂ Archives and Library of Ternate, should motivate employees about the importanceÂ of the information available at the Regional Library. Keywords : Semangat kerja, Minat Baca Masyarakat